Review of guidelines in general eye screening program / Akmal Kamaliah Badrulhisham - Badrulhisham, Akmal Kamaliah (Faculty of Health Sciences, 2015)
The standard guidelines of general eye screening program in countries are still questionable due to the presence of contradiction in the factors influencing eye screening program such as target age, appropriate test included and referral criteria for comprehensive eye examination. The objective of this study is to review the pattern of the eye screening programs in Malaysia and other countries based on the factors mentioned previously. This is a systematic review type of research based on the study about eye screening program in Malaysia and other countries that have been released to the public. This research was conducted by reviewing the eye screening program published in reliable journal. These three factors were analysed and presented in the table respectively to each country as a guideline to identify the suitability of particular procedure to be implemented. Most countries have initiated eye screening program at preschool and middle childhood whereas half of the countries performed screening at younger years (infants). Moreover, there were also limited numbers of eye screening conducted at age 19 and above. In optometric screening tests this study has suggested that parental questionnaire, gross eye examination and red reflex are the common preliminary tests for the eye screening of 5 year-old subject and below while the strabismus detection is included in all group of age as binocular assessment. Fixate-following test were done on children younger than 3 years or any illiterate child whereas the visual illiterate. Most referral criteria in preliminary test and binocular assessment are similar in all stage of age excluding vision assessment. In conclusion this review might be helpful and important in constructing the guidelines for optometrists or examiner as an effort to serve the best chances of early detection of visual problems even though there are different kinds of approach in eye screening program.